Design, Realization, and Assessment of a High-Fidelity Physical Simulator for the Investigation of Childbirth-Induced Pelvic Floor Damage - Giulia Modarelli; Sabina Maglio; Paolo Mannella; Selene Tognarelli; Arianna Menciassi (IEEE Access, 2023)
Vaginal delivery is one of the main causes of pelvic floor damage, which can lead to short- and long-term clinical consequences called pelvic floor dysfunctions. The number of women affected by this pathology is continuously rising, representing both a medical issue and an important financial burden. Prevention represents the best strategy of care, but it requires a deep understanding of the injury mechanisms, which is currently lacking. Simulation can help to identify the main factors affecting a clinical event, reducing the need for in vivo investigations. However, current simulators poorly mimic the pelvic structures and do not provide any feedback. These limitations led to the development of an innovative high-fidelity physical simulator to study the mechanisms behind pelvic floor damage caused by vaginal delivery. Anatomically correct gynecological structures were realized using soft materials able to resemble human tissue behavior. Ad hoc stretch sensors were realized with conductive fabric and integrated into the simulator to evaluate tissue elongation caused by the passage of the fetal head. Evaluation of the simulator was carried out both in laboratory conditions and by involving expert clinicians. Gynecologists determined that the simulator is a valid teaching and training tool that is able to provide feedback on instantaneous pelvic floor elongation, thus potentially preventing induced tissue damage.